2018
DOI: 10.1007/s11356-017-1158-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water cadmium concentration and water level on the growth performance of Salix triandroides cuttings

Abstract: The growth performance of Salix triandroides cuttings at three water cadmium (Cd) concentrations (0, 20, and 40 mg L) and three water levels (- 40 cm, water level 40 cm below the soil surface; 0 cm, water level even with the soil surface; and 40 cm, water level 40 cm above soil surface) was investigated to evaluate its potential in phytoextraction strategies. Compared to cuttings in the - 40 or 0 cm water levels, cuttings in the 40 cm water level showed significantly lower biomass, height, and adventitious roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…Translocation factor was always < 1 for both species in all treatments with a decrease at the higher cadmium concentration in S. alba (Table 1). This was in agreement with Yao et al (2018) but in contrast with data reported in literature for other Salix species (Zacchini et al, 2009). Differences were significant in function of species (F= 56.69, p<0.01), metal concentration (F= 34.09, p<0.01), time of treatment (F= 47.47, p<0.01) and interaction among the three factors (F=14.73, p<0.01).…”
Section: Accepted Manuscriptsupporting
confidence: 89%
“…Translocation factor was always < 1 for both species in all treatments with a decrease at the higher cadmium concentration in S. alba (Table 1). This was in agreement with Yao et al (2018) but in contrast with data reported in literature for other Salix species (Zacchini et al, 2009). Differences were significant in function of species (F= 56.69, p<0.01), metal concentration (F= 34.09, p<0.01), time of treatment (F= 47.47, p<0.01) and interaction among the three factors (F=14.73, p<0.01).…”
Section: Accepted Manuscriptsupporting
confidence: 89%
“…The Cd­(II) removal performance of mackinawite nanocrystals was investigated using batch experiments. To simulate the high Cd­(II)-contaminated wastewater (e.g., metallurgy and mining wastewater), a Cd­(II) solution at an initial concentration of 30 mg/L was prepared. Typically, the mackinawite nanocrystals (0.1 g L –1 ) were added into 50 mL conical flasks containing 30 mg L –1 Cd­(II) contaminated solution, with the initial pH adjusted to 6.0 by dilute hydrochloric acid. The flasks were then shaken at 200 rpm at 25 °C for sorption.…”
Section: Methodsmentioning
confidence: 99%
“…The abundance of Cd for plants is influenced by a number of factors, including soil pH, redox potential, soil organic matter, and so on (Chen et al, 2016; Das et al, 2020). Besides this, Cd toxicity also disrupts gas exchange, stomatal conductance, transpiration rate, photosynthesis damage, enzyme inactivation, and protein metabolism in plants (Naeem et al, 2018; Wang et al, 2014; Yao et al, 2018). Hence, the effect of Cd is detrimental to plants and the Cd concentration in cells needs to be adjusted to maintain plant growth and development.…”
Section: Introductionmentioning
confidence: 99%